Avaliação da biocompatibilidade de cimentos endodônticos em tecido subcutâneo de rato e sua relação com o subtipo de macrófago M1 - Miyagaki, Daniela Cristina (2011)
Consedering that the contact between the toxic components present in some endodontic sealers and periradicular tissues can lead to a longer inflammatory reaction, increasing the time required to repair, resulting in postoperative pain and even reactions of delayed type hypersensitivity.The purpose of this study was to evaluate the tissue response of freshly mixed Sealer 26 and Epiphany root canal sealers in early periods after implantation in subcutaneous tissue of rats and analyze the relationship between macrophages M1 and tissue repair. Polyethylene tubes were filled with the test materials and implanted into two different pockets of the dorsum of twenty-one Wistar rats. After 7, 14 and 21 days, seven animals were killed and the implants were removed. Half of the histological sections were processed for hematoxilin and eosin and the rest were stained by means of immunohistochemistry. For each experimental period and sealer, the intensity of inflammatory response was classified according to criteria stablished by the FDI, and the cells positive for iNOS were analized qualitatively and quantitatively, and then subjected to the statistical analysis. The connective tissue response along the lateral wall outside of each tube served as a negative control for the study. A severe inflammatory reaction was observed for both sealers which diminished with time. The immunolabeling showed a variable cytoplasmatic staining for both sealers, along the field and according to the period of analysis. There was a statistically significant difference between Sealer 26 and Epiphany at 7 and 14 days (p = 0.0079 and p = 0.0115, respectively), but in 21 days no significant difference was found (p = 0.6545). Over time, Epiphany showed a greater number of cells positive for iNOS at 14 days, presenting significant differences when compared to periods of 7 (p= 0.0246) and 21 days (p= 0.5212), while Sealer 26 showed no significance (p= 0.3126). It was possible to conclude that Epiphany and Sealer 26 demontraded patterns of acceptability within the initial periods evaluated. Although the immunolabeling for M1 has no direct relationship with the intensity of inflammation and velocity of repair, we suggest that the composition of the sealers results in different ways pf conducting to repair.